Snake predators of bird eggs: a review and bibliography - Jody M. Barends; Bryan Maritz (Journal of Field Ornithology, 2022)
Snakes are frequent predators of bird nests and therefore potentially have an important impact on bird population dynamics. However, while many species are known to consume nestlings and chicks, few species have been recorded consuming bird eggs. To effectively quantify the effects of bird egg predation by snakes on bird demographics, a key first step is to identify which snake species consume bird eggs. Unfortunately, detailed information on the dietary habits of most snakes is scarce and feeding records are poorly cataloged, making it difficult to ascertain which species do and do not eat bird eggs. We reviewed the literature and online community science reports to compile a global list of confirmed snake predators of bird eggs. In total, we gathered 471 feeding records of 123 snake taxa consuming the eggs of at least 210 bird species from 238 individual data sources. Geographical locations of records disproportionately represented well-sampled regions, and we infer that many snake species not included on our list also consume bird eggs. However, we found that oophagous snakes tend to be long (mean maximum length = 2057 mm) and mostly eat eggs that are small in diameter (mean egg diameter = 24 mm), suggesting that relative prey bulk is an important constraint of these interactions. Therefore, we expect that other snakes that eat birds are likely to mostly include congeneric and ecologically similar species to those reflected in our review. By knowing which snakes consume bird eggs, future research can consider species- and site-specific hypotheses when investigating the ecological effects of bird egg predation by snakes. Those results can also inform conservation practitioners on the causes and consequences of variation in nest success that may aid in decision-making when designing conservation management plans.